Comparison of depressive symptoms and eating behaviors among Japanese university students with subthreshold depression before and during the COVID-19 pandemic - Miyake, Yoshie; Takagaki, Koki; Yoshino, Atsuo; Okamoto, Yuri (Frontiers in Psychiatry, 2025)
BackgroundThe COVID-19 pandemic had exposed university students to unusual environmental stresses. High stress levels have been reported among adolescents with depressive symptoms. Subthreshold depression is highly prevalent among university students who are at high risk of developing clinical depression and other psychiatric disorders such as eating disorders. Therefore, this study aimed to investigate the effects of the pandemic on depressive symptoms and eating behaviors among Japanese university students with subthreshold depression from a cohort study.MethodsA total of 555 fourth-year university students, 261 students before the pandemic and 294 students during the pandemic, were participated. The inclusion criteria were age 18–19 years and subthreshold depression upon entering the university and completed questionnaires at both university entrance and during their fourth year. We examined differences in depressive symptoms (Beck Depression Inventory II), eating behaviors (Eating Attitudes Test-26 and Bulimic Inventory Test, Edinburgh [BITE]), stress coping (Coping Inventory for Stressful Situations [CISS]), and the frequencies of the three depression groups (clinical, subthreshold, and healthy) before and during the pandemic. We also investigated the relationship between changes in depression and stress coping during the pandemic.ResultsThere was no significant differences in depression frequency in the fourth year before and during the pandemic. However, the two-way ANOVA on the grade and time revealed significant interaction effects on the BITE scores for females (p < 0.05), and the BITE scores were significantly higher for fourth-year female students during the pandemic than those when they entered the university. Although a decrease in the CISS-emotion-oriented score was associated with a reduction in depressive symptoms both before and during the pandemic, a decrease in the CISS-task-oriented score was associated with an increased risk of depressive symptoms during the pandemic only in males.ConclusionOur results suggest that not only depressive but also bulimic symptoms should have been monitored among university students with subthreshold depression during the pandemic. Attention to stress-coping behaviors may be important for interventions to prevent the deterioration from subthreshold depression to clinical depression during a pandemic. However, the results could have been affected by many other factors, and further research is required.